Health Problem in Indian Urban Women: Yoga as a Solution: Addressing Pollution and Oral Health Issues in Urban Indian Women (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is sixth biggest country by area and the second most populated country. Today we see Air pollution, Soil pollution and Water pollution with poor oral Health awareness.